Evaluation of various RNA-seq approaches for identification of gene outrons in the flatworm Opisthorchis felineus - N. I. Ershov; D. E. Maslov; N. P. Bondar (Вавиловский журнал генетики и селекции)
The parasitic flatworm Opisthorchis felineus is one of the causative agents of opisthorchiasis in humans. Recently, we assembled the O. felineus genome, but the correct genome annotation by means of standard methods was hampered by the presence of spliced leader trans-splicing (SLTS). As a result of SLTS, the original 5’-end (outron) of the transcripts is replaced by a short spliced leader sequence donated from a specialized SL RNA. SLTS is involved in the RNA processing of more than half of O. felineus genes, making it hard to determine the structure of outrons and bona fide transcription start sites of the corresponding genes and operons, being based solely on mRNA-seq data. In the current study, we tested various experimental approaches for identifying the sequences of outrons in O. felineus using massive parallel sequencing. Two of them were developed by us for targeted sequencing of already processed branched outrons. One was based on sequence-specific reverse transcription from the SL intron toward the 5’-end of the Y-branched outron. The other used outron hybridization with an immobilized single-stranded DNA probe complementary to the SL intron. Additionally, two approaches to the sequencing of rRNA-depleted total RNA were used, allowing the identification of a wider range of transcripts compared to mRNAseq. One is based on the enzymatic elimination of overrepresented cDNAs, the other utilizes exonucleolytic degradation of uncapped RNA by Terminator enzyme. By using the outron-targeting methods, we were not able to obtain the enrichment of RNA preparations by processed outrons, which is most likely indicative of a rapid turnover of these trans-splicing intermediate products. Of the two rRNA depletion methods, a method based on the enzymatic normalization of cDNA (Zymo-Seq RiboFree) showed high efficiency. Compared to mRNA-seq, it provides an approximately twofold increase in the fraction of reads originating from outrons and introns. The results suggest that unprocessed nascent transcripts are the main source of outron sequences in the RNA pool of O. felineus.